Z pustynnego piekła do górskiego raju…Żołnierze Armii Krajowej i obywatele polscy w sowieckim obozie dla internowanych NKWD nr 520 w Groznym - Rogut, Dariusz (1972– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
To establish communist rule in Poland, the Soviet occupation forces conducted mass arrests of Poles and Polish citizens. Those detained were suspected of being involved with independence organisations or of collaborating with the German occupiers. Many of these individuals were taken to camps deep within the territory of the Soviet Union, including NKVD camp no. 520 in Grozny. This camp was initially a control and filtration facility but was later repurposed as a detention centre for the contingent of the internees-arrested of the ‘B’ group. Poles were sent to this camp to help improve their physical and mental well-being, which is why the provisions there were relatively good. However, their stay was only a temporary phase in the counter-intelligence operations targeting the internees, with more extensive procedures in subsequent camps.
p. 5-204
Summary in English and Russian.
Keywords: Polish people - persecution - Soviet Union; concentration camps - Soviet Union; GUPVI - history; World War, 1939-1945 - prisoners and prisons, Soviet - history; prisoners of war - Soviet Union - history; Poles; Home Army (AK); Polish citizens; Soviet camps; Soviet repression; internment camps; internees-arrested; group ‘B’; GUPVI of the NKVD; Grozny